Effect of grafting yield and molecular weight of m‐TMI‐grafted‐PP on the mechanical properties of wood fiber filled polypropylene composites. Issue 46 (9th August 2016) - Kale, Amey; Raghu, N.; Natu, H.P.; Aggarwal, Pankaj; Chauhan, Shakti
ABSTRACT: m‐Isopropenyl‐α, α‐dimethylbenzyl isocyanate (m‐TMI) was grafted on isotactic polypropylene (PP) using di‐cumyl peroxide as a reaction initiator under varying reaction conditions to yield m‐TMI‐ g ‐PP coupling agent with four sets of grafting yield and molecular weight. Grafting yield of the synthesized m‐TMI‐ g ‐PP were 1.80%, 2.01%, 9.05%, and 8.86% and molecular weight of the corresponding grafted polymer were 129, 225; [Correction made here after initial online publication.] 187, 240; 124, 130; and 180, 838, respectively. Rubberwood flour reinforced polypropylene composites were prepared using these coupling agents and tested for mechanical properties. m‐TMI‐ g ‐PP coupling agent with 9.09% grafting and 124230 Mw was found to give the highest tensile and flexural strengths. Flexural modulus of the coupled composites was higher than uncoupled composites. Interfacial region of the composites characterized by scanning electron microscope (SEM) suggest effective wetting of fiber by PP in the case of coupled composites. The effect of fiber loading on composites indicates continuous increment in tensile and flexural strengths in coupled composites. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2016, 133, 44196. Abstract :